The Effects of Stunting And Psychosocial Stimulus On The Development of Children Between The Age Of 2- 6 Years Old - Candra Dewi Nataningtyas; Dian Kumalasari (STRADA : Jurnal Ilmiah Kesehatan, 2020)
Nutritional problems is the high rate of children under five with stunted physical development.This research aims to analyze the effects of stunting and psychosocial stimulation on the development of children between the ages of 2-6 years old.This is a observational analytical research with a case control approach, on a sample of 60 children of 2-6 years old.The degree of stunting is assessed using Z-score indicator,calculating children physical height per age.Meanwhile, for psychosocial stimulation, it is obtained through questionnaire filled by parents or caregivers. Children development is measured using Pre-Screening Developmental Questionnaire. Analyzed using chi-square test and logistic regression. Statistically, the sig. value according to chi-square test is 0,000. This value is smaller than 0,05, which can be concluded that stunting and psychosocial stimulus significantly affect child development. The result of multivariate test indicates that stunting and psychosocial stimulation variables have a significant influence on the development of a child (p<0,05).